Analisis faktor-faktor yang mempengaruhi akuntabilitas kinerja instansi pemerintah (akip) kota surakarta(studi pada satuan kerja perangkat daerah kota surakarta) - Biworotomo, Danan, Dr. Zulfikar, SE, MSi (2016)
This present study aims to examine and analyze the factors that affect performance accountability of government agencies (AKIP) Surakarta. The sampel was determined using purposive sampling technique, The criteria of sampel is Head of finance and financial staff. The analysis tool in this research is Multiple Linear Regression Analysis. Samples were 41 employees working at SKPD Surakarta as Head of finance and financial staff. Data were collected using a questionnaire and analyzed using multiple regression analysis by SPSS. The results of study showed that the implementation of accrual accounting, budget goal clarity, reporting system, competence of the officers and adherence to the rule of laws contributed performance accountability of government agencies Surakarta, while based budget performance and accounting controls do not affect the performance accountability of government agencies (AKIP).